Problematization of sexual violence against women in contexts of conflict and displacement: a coherence analysis of the proposed policies in Colombia: Recipient of the I SEGIB (Secretaría General Iberoamericana) Award on Sustainable Development in Ibero-America - Inguanzo, Isabel; Rodríguez-Rodríguez, Angélica (Iberoamerican Journal of Development Studies, 2019)
Previous studies have shown that displaced women suffer more sexual violence than other female populations in the world. In this article, it is analysed how this social problem is defined in Colombia and to what extent there is coherence between the causes identified and the preventive measures proposed to end it. Through N-Vivo software, we perform a content analysis of the judicial decrees issued by the Constitutional Court between 2008 and 2015 about the situation of internally displaced people within the context of the armed conflict. Findings suggest that, when addressing sexual violence, most judicial decrees identify armed actors as the main perpetrators of sexual violence and that when identifying risk factors, judicial decrees tend to stress the importance of the socio-demographic profile of the people attacked rather than the structural causes of the phenomena. Preventive measures are partially coherent with the diagnosis performed; however, some of them are not the most effective ones according to the specialized literature.
Keywords: sexual violence; displaced persons; Colombia; content analysis; policy